Nanocomposites of Chitosan/Graphene Oxide/Titanium Dioxide Nanoparticles/Blackberry Waste Extract as Potential Bone Substitutes - Carlos Humberto Valencia-Llano (MDPI AG, 2021)
New technologies based on nanocomposites of biopolymers and nanoparticles inspired by the nature of bone structure have accelerated their application in regenerative medicine, thanks to the introduction of reinforcing properties. Our research incorporated chitosan (CS) covalently crosslinked with glutaraldehyde (GLA) beads with graphene oxide (GO) nanosheets, titanium dioxide nanoparticles (TiO2), and blackberry processing waste extract (BBE) and evaluated them as partial bone substitutes. Skullbone defects in biomodels filled with the scaffolds showed evidence through light microscopy, scanning electron microscopy, histological studies, soft tissue development with hair recovery, and absence of necrotic areas or aggressive infectious response of the immune system after 90 days of implantation. More interestingly, newly formed bone was evidenced by elemental analysis and Masson trichromacy analysis, which demonstrated a possible osteoinductive effect from the beads using the critical size defect experimental design in the biomodels. The results of this research are auspicious for the development of bone substitutes and evidence that the technologies for tissue regeneration, including chitosan nanocomposites, are beneficial for the adhesion and proliferation of bone cells.